Aerodynamic drag and biomechanical power of a track cyclist as a function of shoulder and torso angles - Underwood, L.; Schumacher, J.; Burette-Pommay, J.; Jermy, M. (Sports Engineering, 2011)
The speed attained by a track cyclist is strongly influenced by aerodynamic drag, being the major retarding force in track events of more than 200 m. The aims of this study were to determine the effect of changes in shoulder and torso angles on the aerodynamic drag and power output of a track cyclist. The drag of three competitive track cyclists was measured in a wind tunnel at 40 kph. Changes in shoulder and torso angles were made using a custom adjustable handlebar setup. The power output was measured for each position using an SRM Power Meter. The power required by each athlete to maintain a specific speed in each position was calculated, which enabled the surplus power in each position to be determined. The results showed that torso angle influenced the drag area and shoulder angle influenced the power output, and that a low torso angle and middle shoulder angle optimised the surplus power. However, the lowest possible torso angle was not always the best position. Although differences between individual riders was seen, there was a strong correlation between torso angle and drag area.